Zamzam Water Surpasses Global Standards in Quality and Mineral Content: Air Zamzam Melampaui Standar Global dalam Kualitas dan Kandungan Mineral - Abed Sultan Hassan; Nadia Abd Ellatif Ali (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the physical, chemical, and bacteriological properties of Zamzam tap water and two popular bottled waters,